Association between breast cancer genetic susceptibility variants and terminal duct lobular unit involution of the breast. Issue 4 (18th November 2016) - Bodelon, Clara; Oh, Hannah; Chatterjee, Nilanjan; Garcia‐Closas, Montserrat; Palakal, Maya; Sherman, Mark E.; Pfeiffer, Ruth M.; Geller, Berta M.; Vacek, Pamela M.; Weaver, Donald L.; Chicoine, Rachael E.; Papathomas, Daphne; et al.
Abstract : Terminal duct lobular units (TDLUs) are the predominant source of future breast cancers, and lack of TDLU involution (higher TDLU counts, higher acini count per TDLU and the product of the two) is a breast cancer risk factor. Numerous breast cancer susceptibility single nucleotide polymorphisms (SNPs) have been identified, but whether they are associated with TDLU involution is unknown. In a pooled analysis of 872 women from two studies, we investigated 62 established breast cancer SNPs and relationships with TDLU involution. Poisson regression models with robust variance were used to calculate adjusted per‐allele relative risks (with the non‐breast cancer risk allele as the referent) and 95% confidence intervals between TDLU measures and each SNP. All statistical tests were two‐sided; P < 0.05 was considered statistically significant. Overall, 36 SNPs (58.1%) were related to higher TDLU counts although this was not statistically significant ( p = 0.25). Six of the 62 SNPs (9.7%) were nominally associated with at least one TDLU measure: rs616488 ( PEX14), rs11242675 ( FOXQ1 ) and rs6001930 ( MKL1) were associated with higher TDLU count ( p = 0.047, 0.045 and 0.031, respectively); rs1353747 ( PDE4D ) and rs6472903 ( 8q21.11 ) were associated with higher acini count per TDLU ( p = 0.007 and 0.027, respectively); and rs1353747 ( PDE4D ) and rs204247 ( RANBP9 ) were associated with the product of TDLU and acini counts ( p = 0.024 and 0.017, respectively). Our findings suggest breast cancer SNPs may not strongly influence TDLU involution. Agnostic genome‐wide association studies of TDLU involution may provide new insights on its biologic underpinnings and breast cancer susceptibility. Abstract : What's new? As women age, the ducts in their breasts that produce milk, called TDLUs, begin to shrink and disappear. However, when they disappear more slowly than normal, it may signal an increased risk of breast cancer. These authors wanted to know whether genetic loci linked to breast cancer also relate to TDLU shrinkage. They pooled data from two studies to investigate whether any of 62 breast cancer susceptibility loci were associated with TDLU shrinkage measures. Six SNPs showed a nominal association, but it was not evident that breast cancer genes did influence TDLU appearance.